Juridical Analysis of Inheritance Rights of Foreign-National Children Born from Mixed Marriages under the Indonesian Civil Code - Aprilia Widya Mandey; Linda Lidia Imon (Journal Social Civilecial, 2026)
Mixed marriages between Indonesian citizens and foreign nationals create complex legal consequences for children, particularly when citizenship status intersects with inheritance and property ownership. This study examines the legal status of children born from mixed marriages and analyzes their inheritance rights when they hold or later choose foreign nationality. Using a normative juridical method, the research applies statutory and conceptual approaches to Indonesian marriage law, citizenship law, civil inheritance law, child protection law, and agrarian law. The analysis shows that Law No. 12 of 2006 provides limited dual citizenship for children born from mixed marriages until the age of 18 or marriage, followed by a three-year period to choose one citizenship. Under the Indonesian Civil Code, a child born from a valid mixed marriage remains a legitimate heir where a lawful civil relationship with the deceased parent exists. Foreign nationality does not automatically eliminate the right to inherit. However, agrarian law restricts foreign nationals from permanently holding ownership-title land in Indonesia. A foreign-national heir who receives such land must transfer, release, convert, or realize its value within the legally prescribed period. The study clarifies the distinction between inheritance entitlement and ownership capacity, contributing to legal certainty in cross-border family inheritance disputes.